Changes in the fecal bacterial microbiota associated with disease severity in alcoholic hepatitis patients. Issue 1 (9th November 2020) - Lang, Sonja; Fairfied, Bradley; Gao, Bei; Duan, Yi; Zhang, Xinlian; Fouts, Derrick E.; Schnabl, Bernd
ABSTRACT: Background and Aims: Alcoholic hepatitis is the most severe form of alcohol-related liver disease. While the gut microbiome is known to play a role in disease development and progression, less is known about specific compositional changes of the gut bacterial microbiome associated with disease severity. Therefore, the aim of our study was to correlate gut microbiota features with disease severity in alcoholic hepatitis patients. Methods: We used 16S rRNA gene sequencing on fecal samples from 74 alcoholic hepatitis patients, which were enrolled at 9 centers in Europe, the United States, and Mexico in a multi-center observational study. The relative abundance of gut bacterial taxa on genus level, as well as the microbiome diversity, was correlated to various clinical, laboratory, and histologic parameters. Results: We observed a negative correlation between the model for end-stage liver disease score and Shannon diversity, independent of potentially confounding factors (Padjust = 0.046). Alcoholic hepatitis patients with more severe disease had significantly decreased relative abundances of Akkermansia while the relative abundance of Veillonella was increased. We observed a reduction in the Bacteroides abundance (Padjust = 0.048) and Shannon diversity (Padjust = 0.018) in antibiotic-treated patients and patients receiving steroids had an increase in Veillonella abundance (Padjust = 0.005), which was both independent of potentially confounding factors. Conclusion: We observed distinct changes in the gut bacterial microbiome of alcoholic hepatitis patients with more severe disease. The gut bacterial microbiome might be an attractive target to prevent and treat this deadly disease.